Oral narrative research with Black women - Vaz, Kim Marie (Sage Publications, 1997)
Oral narrative researchers from a range of disciplines present their personal portraits on the methodological strategies they have found useful in bringing the experiences of African and African American women into full view. This insightful and thought-provoking resource explores in detail: how new information about African women is being created; the strengths of oral narrative research for expanding and transforming knowledge about black women; and how carrying out oral history research has affected the researchers' personal and professional lives.